ANALISA PERBANDINGAN APLIKASI PENDETEKSI PHOTO MENGGUNAKAN METODE EMPIRIS - Rendra Soekarta; Aprisa Rian Histiarini; Achmad Saiku Wadianto (Metode : Jurnal Teknik Industri, 2020)
Computers as a tool to complete a job using a computer has become a common thing in the eyes of the public, in general computers are used to do work in technology and information such as inputting data, storing information, and even modifying or taking a photo. Because computers are often used to help or facilitate a business, it is not uncommon for computers to be used by users, especially in the case of image falsification in order to achieve a goal of course this can be detrimental to various parties. In terms of obtaining correct information, it is not uncommon for many new applications to be created to assist users in determining which photos are real or fake, using empirical methods which analyze both photo detection applications based on the observations and experiences of researchers.